(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The general objective will be to expose the reports described in the book-reportage Holocausto Brasileiro by journalist Daniela Arbex, (main object) and to relate to the utilitarian theory, in order to verify its application, both by the society in general and by the public power. It will be analyzed from the perspective of utilitarian theory, however, many times in order to obtain happiness, we sacrifice the minority. Historically, society punishes members who do not fit the standard. In this way, the spectacularization of society at the time, which did nothing in relation to the abuses committed there, will now be analyzed, and it is now up to the State to recognize its responsibility, whether in the light of human rights, as well as in national and international legislation. Finally, the discourse analysis methodology was used with a qualitative approach. as a bibliographic research.